Persistent Cutaneous Papules and Nodules in a Six-year-old Child: A Quiz - Jeanette Halskou Haugaard; Lone Skov; Signe Ledou Nielsen; Hans Christian Ring (Medical Journals Sweden, 2022)
Abstract is missing (Quiz)